FUNERAL RITE «GRUSHKA» IN HUTSUL TEXT BY MYKHAILO KOTSIUBYNSKYI, MARKO CHEREMSHYNA AND PETRO SHEKERYK-DONYKIV - Salii, O. R. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
The article deals with death as a phenomenon that is firmly rooted in the Hutsul culture and their philosophy of life. Therefore, all writers who had written about this region developed the theme of death in their works. The Hutsuls lived in a cycle of ritual-magical time, where death was a natural phenomenon. That`s why one of the important elements of their funeral rites was ritual playing near the deceased, and some of this playing were erotic. This ritual, in which soreness was intertwined with fun and death with life, was introduced into the subject of novellas by M. Kotsiubynskyі, Marko Cheremshyna and P. Shekerik-Donykіv. So this is a study of how each of them treated the topic, why this funeral rite was important, what it meant to the Hutsuls at once time and what significance have as an element of the Hutsul text today.